2017
DOI: 10.2105/ajph.2017.303941
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Despair Among White Americans: Trends in the Leading Causes of Premature Death, 1999–2015

Abstract: The unfavorable recent trends in premature death rate among non-Hispanic Whites outside large urban areas were primarily caused by self-destructive health behaviors likely related to underlying social and economic factors in these communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
189
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(199 citation statements)
references
References 17 publications
8
189
2
Order By: Relevance
“…Prior studies have documented adverse trends in mortality related to poisonings, liver cirrhosis, and suicide within particular age groups (Case and Deaton , ; Stein et al. ). We find that among these causes, drug overdose makes the largest contribution to trends in life expectancy between 1990–1992 and 2014–2016 in all metro categories and all regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have documented adverse trends in mortality related to poisonings, liver cirrhosis, and suicide within particular age groups (Case and Deaton , ; Stein et al. ). We find that among these causes, drug overdose makes the largest contribution to trends in life expectancy between 1990–1992 and 2014–2016 in all metro categories and all regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…; Stein et al. ). The underlying mechanisms driving mortality trends for non‐Hispanic whites are fundamentally different from those driving trends for other racial/ethnic groups, as suggested by James and Cossman (2017).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…5,17 It is expected that this varies across cancer sites based on various emotional trauma and psychosocial issues associated with cancer sites. 20 Results also Cancer October 15,2018 have been inconsistent because of small sample sizes, methodology, or study bias. 20 Results also Cancer October 15,2018 have been inconsistent because of small sample sizes, methodology, or study bias.…”
Section: Introductionmentioning
confidence: 99%
“…For example, three US‐based studies included in a recent meta‐analysis suggested lower prevalence of depression among rural versus urban older adults . However, other recent US studies have revealed increasing rates of suicide and alcohol‐related and drug‐related deaths in rural and sparsely populated regions, suggesting that mental health outcomes may disproportionately burden these areas. Our results add to this growing literature on geographic health disparities by suggesting that the prevalence of elevated depressive symptoms may be higher among participants who lived in the rural United States during childhood.…”
Section: Discussionmentioning
confidence: 99%